Single-use plastic and COVID-19 in the NHS: Barriers and opportunities - Xiaocheng Hu; Roz Davies; Karyn Morrissey; Richard Smith; Lora E. Fleming; Maria Sharmina; Rebecca St. Clair; Peter Hopkinson (SAGE Publishing, 2021)
Background: Single-use personal protective equipment (PPE) has been essential to protect healthcare workers during the COVID-19 pandemic. However, intensified use of PPE could counteract the previous efforts made by the UK NHS Trusts to reduce their plastic footprint. Design and methods: In this study, we conducted an in-depth case study in the Royal Cornwall Hospitals NHS Trust to investigate plastic-related issues in a typical NHS Trust before, during and after the pandemic. We first collected hospital routine data on both procurement and usage of single-use PPE (including face masks, aprons, and gowns) for the time period between April 2019 and August 2020. We then interviewed 12 hospital staff across a wide remit, from senior managers to consultants, nurses and catering staff, to gather qualitative evidence on the overall impact of COVID-19 on the Trust regarding plastic use. Results: We found that although COVID-19 had increased the procurement and the use of single-use plastic substantially during the pandemic, it did not appear to have changed the focus of the hospital on implementing measures to reduce single-use plastic in the long term. We then discussed the barriers and opportunities to tackle plastic issues within the NHS in the post-COVID world, for example, a circular healthcare model. Conclusion: investment is needed in technologies and processes that can recycle and reuse a wider range of single-use plastics, and innovate sustainable alternatives to replace single-use consumables used in the NHS to construct a fully operational closed material loop healthcare system.